Interconexión entre religiosidad y comunicación deportiva en las redes sociales: la perspectiva de los musulmanes indonesios (Interconnection between religiosity and sports communication on social media: an indonesian muslims’ perspective) - Hafiar, Hanny; Subekti, Priyo; Prastowo, Ari Agung; Amin, Kholidil; Kusmayadi, Ika Merdekawati; Mirawati, Ira; Purnomo, Eko; Abdullah, Khairul Hafezad (Retos, 2024)
Abstract. Religion shapes beliefs, values, and normative social systems in society. Religiosity often becomes a driving factor for Muslims in making preferences for sports. Indonesia, a country with the largest Muslim societies in the world, is deemed to have the potential for sports communication with Islamic values. Social media allows athletes to develop a specific image through common religious values with their fans. This study aimed to measure the effect of religiosity and athlete brand image on the intentions of Indonesian Muslim fans to follow the athlete's Instagram account with a religious image. A cross-sectional survey in Indonesia was conducted with 1245 football fans. The collected data was analyzed using Partial Least Square-Structural Equation Modelling with SmartPLS software. The result indicated that religiosity and athlete branding image could predict Muslim fans’ intention to follow the Instagram accounts of religious football athletes. This finding suggested the importance of strategic management of athlete branding image through social media accounts, such as developing an image by religious approach among Indonesian Muslim fans.Keywords: Religiosity, Indonesian Muslim society, brand image, social media, digital generation.